Flos puerariae ameliorates the intestinal inflammation of Drosophila via modulating the Nrf2/Keap1, JAK-STAT and Wnt signaling - Yang, Shipei; Li, Xu; Xiu, Minghui; Dai, Yuting; Wan, Shengfang; Shi, Yan; Liu, Yongqi; He, Jianzheng (Frontiers in Pharmacology, 2022)
Gut homeostasis is important for human health, and its disruption can lead to inflammatory bowel disease (IBD). Flos Puerariae is a herb with a wide variety of pharmacological activities including antioxidant, antidiabetic, antialcoholismic and anti-inflammatory properties. However, the role of Flos Puerariae on treating IBD remains obscure. Here, we employed Drosophila melanogaster as a model organism to investigate the protective effect of Flos Puerariae extract (FPE) against sodium dodecyl sulfate (SDS)-induced intestinal injury. Our data showed that FPE had no toxic effect in flies, and significantly extended lifespan in SDS-inflamed flies, reduced stem cell proliferation in the midgut, and maintained intestinal morphological integrity. Furthermore, FPE remarkably recused the altered expression level of genes and proteins in Nrf2/Keap1 signaling, JAK-STAT signaling and Wnt signaling pathways in gut of inflammation flies. Thus, FPE has a protective effect against intestinal injury possibly via increasing the Nrf2/keap1 pathway and suppressing the JAK-STAT and Wnt signaling pathways, which would have tremendous potential for treating IBD.